Effects of the COVID-19 Outbreak on Elder Mistreatment and Response in New York City: Initial Lessons. (July 2020) - Elman, Alyssa; Breckman, Risa; Clark, Sunday; Gottesman, Elaine; Rachmuth, Lisa; Reiff, Margaret; Callahan, Jean; Russell, Laura A.; Curtis, Maureen; Solomon, Joy; Lok, Deirdre; Sirey, Jo Anne; et al.
New York City is currently experiencing an outbreak of COVID-19, a highly contagious and potentially deadly virus, which is particularly dangerous for older adults. This pandemic has led to public health policies including social distancing and stay-at-home orders. We explore here the impact of this unique crisis on victims of elder mistreatment and people at risk of victimization. The COVID-19 outbreak has also had a profound impact on the organizations from many sectors that typically respond to protect and serve victims of elder mistreatment. We examine this impact and describe creative solutions developed by these organizations and initial lessons learned in New York City to help inform other communities facing this pandemic and provide guidance for future crises.